Evaluation of the BSA curriculum in selected colleges of agriculture in relation to minimum standards - Ables, Higino
This study was launched to evaluate the Bachelor of Science in Agriculture curriculum in selected colleges of agriculture in the country in relation to the minimum standards set by the Ministry of Education and Culture. A study like this is important and timely to colleges of agriculture and to educators who are interested ion knowing the state of agricultural education in the Philippines and those concerned with the alleviation of its plight.
Keywords: Agricultural education -- Philippines -- Standards; Agricultural education -- Curricula -- Philippines; Agricultural colleges -- Curricula -- Philippines